Fikih Siyasah dan Tantangan Pendidikan Multikultural - Shulha, Irham Fathiyyah (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2020)
The study of looking for a good educational format in a multicultural country like Indonesia will continue to be interesting, because it will experience a number of challenges to be faced. In addition to the challenges of multicultural education in terms of concepts, challenges will also arise in the perspective of the Siyasah Jurisprudence which is interpreted in the Islamic political order because in Indonesia the majority of the population is Muslim. This scientific work aims to answer the problem formulation of the challenges of multicultural education both in terms of concepts and from the point of view of pandanus fiqh siyasah (Islamic politics). The method used in this research is a descriptive research library with a rationalistic qualitative research analysis. The challenge of multicultural education will be the rejection of a group of Muslims who have not fully understood the meaning of multiculturalism. They think that the concept of Multicultural Education that has been initiated is wrong. In the viewpoint of fiqh siyasah, the challenge of multicultural education is in terms of regulations that have no specific (specific) legal umbrella governing the concept of multicultural education oriented to Maqoshidu As-Syari'ah.